Diversity of Soil Insects on Some Stand Types in Gunung Walat University Forest and Its Relationship with Environmental Variables - Cahyo Wibowo; Sylvia Dewi Wulandari (Jurnal Silvikultur Tropika, 2014)
Soil insects play an important role in maintaining forest soil fertility. Soil insects ingest the decomposing organic matter and transform them into simpler substances for plant nutrients and improve soil physical properties (Borror et al. 1992). This study shows that in Gunung Walat University Forest, species Rhinotermitidae 1 (termites), Formicidae (brown ant), and Scarabaeidae (larvae of Coleoptera) possesed the largest abundance in stands of agathis, pine, mixed forest and burnt pine. Soil insect abundance was greatest in agathis stand with low crown density. Insects were more abundant in soil than in litter. Mixed forest stand possesed the largest soil insect diversity as compared with other stand types.